The process of moisture and temperature change of soil profile in Pisha sandstone area. Issue 1 (June 2020) - Zhang, Pan; Sun, Weiying; Xiao, Peiqing; Yang, Chunxia
Abstract: The Pisha sandstone area in Ordos Plateau is a cross zone of water, wind and freeze-thaw erosion. Freeze-thaw erosion is one of the important erosion modes in this area, and soil moisture and temperature are the two key factors affecting it. In order to reveal the change process of soil moisture and temperature with time in the Pisha sandstone area, we took the small watershed of Erlaohugou in Huangfuchuan as the study area. Two sets of EM50 full-automatic collection systems were set up on a typical slope in the area, and the change process of moisture and temperature of the slope from March to September was continuously observed. The results showed that the changes of soil moisture and temperature in this area were greatly affected by seasons and climate. Soil moisture exhibited significant temporal and spatial differentiation, while soil temperature had significant temporal differentiation but not obvious spatial differentiation.